Disorders of Sex Development in South Kalimantan: First Case Reports of a Neonate with 46,XX Virilization and an Adolescent with 46,XY Undervirilization - Niarsari Anugrahing Putri; Indra Widjaya Himawan; Maria Ulfah; Naisya Balela (Rifa'Institute, 2026)
Introduction: Disorders of Sex Development (DSD) are rare congenital conditions with high diagnostic complexity. Objective: To describe the challenges in the diagnosis and management of DSD in South Kalimantan through two case reports. Method: Data were obtained from the medical records of two DSD patients in South Kalimantan. Results and Discussion: Case 1: A 10-day-old 46,XX neonate with ambiguous genitalia (Prader III), hyperkalemia (K 8.8), hyponatremia (Na 134), and hypoglycemia. Salt-wasting Congenital Adrenal Hyperplasia (CAH) was diagnosed (17-OHP 237 ng/mL). Case 2: A 17-year-old raised female with progressive virilization since age nine. Examination showed Prader IV, 7-cm phallus, bilateral testes (10–12 mL), absent Müllerian structures, and 46,XY karyotype, suggesting Partial Androgen Insensitivity Syndrome (PAIS) or 5α-reductase deficiency. Both cases reflect regional limitations: unavailable comprehensive hormonal testing, genetic molecular analysis, and no permanent multidisciplinary DSD team. Conclusions: Limitations in diagnostic resources at the regional level significantly impact the optimization of DSD patient management, necessitating the development of diagnostic capacity and multidisciplinary collaboration